Utility of serum lactate dehydrogenase in the diagnosis of megaloblastic anemia - Gaikwad, Amrapali L.; Jadhav, D. S. (International Journal of Research in Medical Sciences, 2018)
Background: Megaloblastc anemia corresponds to severe macrocytic anemia with hypersegmented neutrophils and very high serum Lactate Dehydrogenase (LDH). The present study was undertaken to evaluate the utility of serum LDH and chloroform inhibited serum LDH in the diagnosis of megaloblastic anemia and to observe if this can be used to differentiate megaloblastic anemia from iron deficiency anemia and hemolytic anemia. Methods: The present study was carried out on 75 patients of anemia categorised on bone marrow examination (into megaloblastic and non-megaloblastic anaemia) to evaluate the efficacy of total serum LDH levels and LDH isoenzyme pattern in the diagnosis of megaloblastic anemia. About 25 healthy adults were taken as controls. Results: In megaloblastic anemia, total serum LDH level was found to be increased to about nineteen folds and in hemolytic anemia it was found to increased four folds as compared to normal. On statistical analysis this increased total serum LDH level in megaloblastic anemia and hemolytic anemia as compared to control group was found to be significant.In the present study serum LDH level above 3000IU/L was associated with megaloblastic anemia and serum LDH level below 900IU/L was suggestive of iron deficiency anemia. The chloroform inhibition test was less than 25% in megaloblastic anemia and more than 25% in hemolytic anemia and these differences were found to be statistically significant (t=9.62, df=49, p<0.001). Conclusions: Total serum LDH levels more than 3000IU/L are diagnostic of megaloblastic anemia. Reversed LDH isoenzyme pattern (LDH1>LDH2) by chloroform inhibition test is an adjuvant in the diagnosis where total serum LDH levels are between 451-3000IU/L and can also differentiate megaloblastic anemia from hemolytic anemia.